Exploration of the core pathway of inflammatory bowel disease complicated with metabolic fatty liver and two-sample Mendelian randomization study of the causal relationships behind the disease - Wei, Zhiyuan; Wang, Jiangbin (Frontiers in Immunology, 2024)
Background: Inflammatory bowel disease (IBD) is often associated with complex extraintestinal manifestations. The incidence of nonalcoholic fatty liver disease (NAFLD) in IBD populations is increasing yearly. However, the mechanism of interaction between NAFLD and IBD is not clear. Consequently, this study aimed to explore the common genetic characteristics of IBD and NAFLD and identify potential therapeutic targets.Materials and Methods: Gene chip datasets for IBD and NAFLD were obtained from the Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was performed to identify modules in those datasets related to IBD and NAFLD. ClueGO was used for biological analysis of the shared genes between IBD and NAFLD. Based on the Human MicroRNA Disease Database (HMDD), microRNAs (miRNAs) common to NAFLD and IBD were obtained. Potential target genes for the miRNAs were predicted using the miRTarbase, miRDB, and TargetScan databases. Two-sample Mendelian randomization (MR) and two-way MR were used to explore the causal relationship between Interleukin-17 (IL-17) and the risk of IBD and NAFLD using data from GWAS retrieved from an open database.Results: Through WGCNA, gene modules of interest were identified. GO enrichment analysis using ClueGO suggested that the abnormal secretion of chemokines may be a common pathophysiological feature of IBD and NAFLD, and that the IL-17-related pathway may be a common key pathway for the pathological changes that occur in IBD and NAFLD. The core differentially expressed genes (DEGs) in IBD and NAFLD were 3 identified and included COL1A1, LUM, CCL22, CCL2, THBS2, COL1A2, MMP9, and CXCL8. Another cohort was used for validation. Finally, analysis of the miRNAs identified potential therapeutic targets. The MR results suggested that although there was no causal relationship between IBD and NAFLD, there were causal relationships between IL-17 and IBD and NAFLD.We established a comorbid model to explain the potential mechanism of IBD with NAFLD and identified the chemokine-related pathway mediated by cytokine IL-17 as the core pathway in IBD with NAFLD, in which miRNA also plays a role and thus provides potential therapeutic targets.